2006
DOI: 10.1111/j.1651-2227.2007.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of smoking in pregnancy on factors influencing fetal growth

Abstract: Smoking during pregnancy causes symmetrical fetal growth impairment, possibly due to decreased oxygen transport to the fetus and decreased concentrations of fetal insulin, insulin-like growth factor I and IGF binding protein 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 29 publications
(34 reference statements)
3
40
1
1
Order By: Relevance
“…17 A study by Kirchengast and Hartmann on the birth outcome of adolescent mothers showed that the offspring of extremely young mothers of age 12-16 years were significantly smaller in all body dimensions compared to the offspring of older adolescent mothers or adult mothers. 15 Lira et al 18 also reported in their cohort study that Brazilian children from taller mothers tended to have a larger head circumference at birth. However, our study reported an unexpected finding that advanced maternal age was associated with a lower risk of microcephaly.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…17 A study by Kirchengast and Hartmann on the birth outcome of adolescent mothers showed that the offspring of extremely young mothers of age 12-16 years were significantly smaller in all body dimensions compared to the offspring of older adolescent mothers or adult mothers. 15 Lira et al 18 also reported in their cohort study that Brazilian children from taller mothers tended to have a larger head circumference at birth. However, our study reported an unexpected finding that advanced maternal age was associated with a lower risk of microcephaly.…”
mentioning
confidence: 92%
“…Maternal age, height, pregnancy weight gain, socioeconomic background, lifestyle, and environmental exposure were identified as significant predictors. [14][15][16][17][18][19] Advancing maternal age, mothers with short stature, and poor weight gain during pregnancy were identified as contributing factors to smaller infant head circumference. [16][17][18] The aims of this study were to establish the trend of head circumference and incidence and predictors of microcephaly among Malaysian term newborns at the Universiti Kebangsaan Malaysia Medical Center (UKMMC) from 2011 to 2015.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been considered as an important risk factor for intrauterine growth retardation (Ingvarsson et al 2007;Aagaard-Tillery et al 2008). Most of the previous studies reveal that mothers who smoke during their pregnancies deliver infants weighing from 100 g to 300 g less than babies born to nonsmoking mothers (Conter et al 1995;Cornelius et al 1995, Cornelius et al 2002.…”
mentioning
confidence: 99%
“…Measurement of hemoglobin concentration, hematocrit levels and serum ferritin levels were used in previous research to determine iron stores in smoking mothers. Based on these parameters, researchers concluded that pregnant smokers have low iron stores, however, they did not directly compare iron status of smokers to nonsmokers (13)(14)(15) and many studies of pregnant women indicate lower iron status, especially when the indicator used to assess iron status is not corrected for the increase in maternal blood volume during pregnancy.…”
Section: Discussionmentioning
confidence: 99%